PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT DI SD 123 PEKANBARU TAHUN 2022 - Situmorang, Hara N.R.E; Juita, Ardiah; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
bstract: The aim is to find out how to implement clean and healthy livingbehavior at SDN 123 Pekanbaru in 2022. The research problem and objectivesdetermine the classification of this research as descriptive research. The place of thisresearch is SDN 123 Pekanbaru which is located on Jl. Mermaid No. 66 TangkerangBarat, Marpoyan Damai District, Pekanbaru City, carried out in July-December 2022.The results of research on the Implementation of Clean and Healthy Living Behavior atSDN 123 Pekanbaru in 2022 show that the Implementation of Clean and Healthy LivingBehavior at SDN 123 Pekanbaru in West 2022 is classified as Good; with an answerpercentage value of 67.56%, this shows that the implementation of Clean and HealthyLiving Behavior at SDN 123 Pekanbaru in 2022 at this school is considered good.Keywords: Implementation, Behavior, Clean and Healthy Living